The nature of mental health nurses' knowledge - Barker, Janet H. (2002)
There is a need to develop a clear understanding of the knowledge used by mental health nurses in day to day practice. Knowledge relating to holistic/therapeutic activities form the basis of mental health nurse education, however various studies have consistently shown the majority of mental health nurses activity relates to administrative and routine tasks and containment. This disparity between the knowledge bases prescribed, those described and the inability of education reforms to resolve such inconsistencies suggests other influences are at work. Concepts of power and knowledge figure largely in the evolution of nursing per se and mental health nursing in particular. Michel Foucault proposes that power forms knowledge and produces discourses. A body of knowledge is not formed by a `subject who knows' but rather through the processes and struggles that transverse that subject. Thus mental health nurses do not produce a regime of knowledge but rather power relations inscribe on the nurse and sustain forms/domains of knowledge.